2009
DOI: 10.1177/104063870902100111
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Phaeohyphomycosis in Weedy Seadragons (Phyllopteryx Taeniolatus) and Leafy Seadragons (Phycodurus Eques) Caused by Species of Exophiala, Including a Novel Species

Abstract: Abstract. During the period from January 2002 to March 2007, infections by melanized fungi were identified with greater frequency in aquarium-maintained leafy seadragons (Phycodurus eques) and weedy seadragons (Phyllopteryx taeniolatus), pivotal species to the educational and environmental concerns of the aquarium industry and conservation groups. The objective of this study was to characterize the pathology and identify fungi associated with phaeohyphomycotic lesions in these species. Samples from 14 weedy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 65 publications
2
69
0
Order By: Relevance
“…Disseminated infections by Exophiala angulospora were identified repeatedly in aquarium-maintained weedy seadragons (Phyllopteryx taeniolatus) (38). A novel species of Exophiala, now described as E. aquamarina, caused infections in leafy seadragons (Phycodurus eques).…”
Section: Fishesmentioning
confidence: 99%
“…Disseminated infections by Exophiala angulospora were identified repeatedly in aquarium-maintained weedy seadragons (Phyllopteryx taeniolatus) (38). A novel species of Exophiala, now described as E. aquamarina, caused infections in leafy seadragons (Phycodurus eques).…”
Section: Fishesmentioning
confidence: 99%
“…Uronema marinum and the microsporidian Glugea heraldi have also been described in syngnathids but have limited to no treatment options, respectively (Koldewey 2005). Significant diseases include mycobacteriosis and Vibrio harveyi septicemia, and fungal exophilalosis (Blazer & Wolke 1979, Koldewey 2005, Nyaoke et al 2009). Herein we report on the gross and histopathologic findings associated with an epizootic of fusariosis in a group of lined seahorses, as well as the molecular identification and phylogenetic characterization of the agent as an unnamed phylogenetic species designated FSSC 12-a Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%
“…19 The lesions consisted of areas of vascular and fibrinoid parenchymal necrosis and granulocytic and histiocytic inflammation with numerous thin-walled, septate fungal hyphae that stain brown in routine HE sections (Fig. 9).…”
Section: Phaeohyphomycosismentioning
confidence: 99%
“…5,8,19,23 Most cases of phaeohyphomycosis were diagnosed by morphology and staining characteristics on light microscopy, although several cases included here were diagnosed by culture and sequencing of PCR-amplified DNA. 19 Similarly, intestinal coccidiosis has been reported to be caused by a novel species of Eimeria in the WSD (Eimeria phyllopterycis). 20,27 Although intestinal coccidiosis was reported in 5 WSD in this study, no cases were found in LSD, which is consistent with the findings in another report.…”
Section: 19mentioning
confidence: 99%